2016
DOI: 10.1111/sms.12741
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness reference standards in fibromyalgia: The al‐Ándalus project

Abstract: We aimed (1) to report age-specific physical fitness levels in people with fibromyalgia of a representative sample from Andalusia; and (2) to compare the fitness levels of people with fibromyalgia with non-fibromyalgia controls. This cross-sectional study included 468 (21 men) patients with fibromyalgia and 360 (55 men) controls. The fibromyalgia sample was geographically representative from southern Spain. Physical fitness was assessed with the Senior Fitness Test battery plus the handgrip test. We applied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
3
19
0
4
Order By: Relevance
“…Comparing the results of our study with normative data, we can observe how the exergame intervention led to obtain a score in the arm curl test, even in dual‐task condition, higher than normative data for fibromyalgia patients. Furthermore, results in the back scratch test are worth mentioning, since significant improvements were only observed under dual‐task condition in that test.…”
Section: Discussionmentioning
confidence: 52%
“…Comparing the results of our study with normative data, we can observe how the exergame intervention led to obtain a score in the arm curl test, even in dual‐task condition, higher than normative data for fibromyalgia patients. Furthermore, results in the back scratch test are worth mentioning, since significant improvements were only observed under dual‐task condition in that test.…”
Section: Discussionmentioning
confidence: 52%
“…32 However, the AG obtained even better values (15.33 ± 3,76 repetitions) than the healthy group 60-64 years of age (14.50 ± 4.0 repetitions) 32 or similar values for Spanish healthy women 40-49 years of age (15.46 ± 2.92 repetitions). 9 According to the reference values of physical fitness in women with FM, 40 the AG is located between 90th and 99th percentile, and the CG is located in 60th percentile.…”
Section: Pre-test Mean (Sd)mentioning
confidence: 99%
“…9 However, the CG achieved the lowest results, below the 25th percentile (14.58 ± 6.35 kg). Specially, taking into account reference values of physical fitness in women with FM, 40 the AG is located between 60th and 70th percentile; however, the CG is located in 30th percentile. Aparicio et al 42 suggested that the handgrip strength test could discriminate between the presence and absence of FM and help determine FM severity in women.…”
Section: P-value (Time × Group) Cohen's D ∆ (Post-test-pre-test)mentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde FMS olan hastalarda fiziksel uygunluk parametrelerinin değerlendirildiği farklı çalışmalar bulunmaktadır (23,24). Ancak bu çalışmalar incelendiğinde aerobik uygunluk, kas kuvveti, esneklik, motor çeviklik gibi parametrelerin değerlendirildiği görülmektedir.…”
Section: İstatistik Analizunclassified